Bismuth sensitized iron oxide on exfoliated graphene oxide (Bi–Fe2O3@GO) for oxygen evaluation reaction - Akhtar Munir; Shaheer Jamal; Humaira Yasmeen Gondal; Javed Iqbal; Aamir Hussain; Arslan Aziz; Mahammad Nisar; Muhammad Zubair; Abdul Momin; Ali Haider (Discover Nano)
Abstract Electrochemical water splitting is a promising approach towards a sustainable and renewable energy source. However, the demand for high anodic potential and sluggish kinetics of oxygen evolution reaction (OER) restrict the efficiency and feasibility of the water-splitting process. In this quest, transition metal oxides and alloys are considered potential candidates owing to their natural occurrence and high redox potential for OER. However, many associated challenges in their use are still there to be addressed. Here, we designed a new class of bismuth-doped iron oxide on exfoliated graphene oxide by optimizing the metal loading on the conductive support to facilitate the flow of charge during catalysis. The catalytic ability of the synthesized Bi-doped nanocomposites was evaluated in activating the OER under extreme alkaline conditions (1 MKOH). On screening different combinations, 20Bi–Fe2O3@GO was identified as the most efficient and sustainable electrocatalyst even under harsh operating conditions, with an onset potential of 1.48 V and a Tafel slope of 65 mV/dec. The current study offers a new class of Bi-doped electrocatalysts, where the precise doping of Bi and the optimized loading of metal was found the key to achieving low onset potential and high current density to initiate OER. Graphical abstract